Effect of Trichoderma sp. on Fusarium Wilt Disease Infection in Banana Plants in Were III Village, Golewa Selatan Sub-District, Ngada District - Lea, Victoria Coo; Noywuli, Nicolaus; Goda, Karina Dhena; Mite, Agnes L.; Limbu, Umbu N. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Ngada Regency area is one of the producers of kapok bananas on Flores Island. However, there has been a decline in kapok banana production due to the attack of blood disease and fusarium wilt. Therefore, it is necessary to address this issue. Determining the effects of applying the biological agent Trichoderma sp. to control fusarium wilt disease in banana plants, comparing the effects of different banana varieties planted on farmer fields infected with the disease, and identifying banana varieties that can interact with the mixed biological agent Trichoderma sp. and organic materials to suppress fusarium wilt disease are the objectives of this study. This study used a factorial pattern Randomized Group Design (RAK) consisting of two factors, namely: Banana type factor (J) consists of 4 levels and the application of Trichoderma sp mixture (D) consists of 4 levels, namely the Banana Type factor (J), consists of 4 levels, namely: J1 = King Banana, J2 = Ambon Banana, J3 = Barangan Banana and J4 = Kepok Banana. A combination of Trichoderma sp and manure application (D) is the second element. There are four levels of this combination: D0 (no Trichoderma sp), D1 (200 gr in 4 kg of manure), D2 (200 gr in 8 kg of manure), and D3 (200 gr in 12 kg of manure). The findings demonstrated that the rate of Fusarium oxysporum wilt infection was significantly influenced by banana species. Compared to plantains and banana kepok, banana barangan and banana ambon are more resilient to the rate of infection with Fusarium wilt disease (Fusarium oxysporum). The combination dose of Trichoderma Sp with manure has a very significant effect on the intensity of Fusarium wilt disease attack (Fusarium oxysporum) and the combination of Trichoderma sp 200 grams with 4 kg of organic fertilizer is better than the other 3 doses.